2021
DOI: 10.3389/fpsyg.2021.593285
|View full text |Cite
|
Sign up to set email alerts
|

The Motor Function Evaluation of College Students’ Physical Activity State From the Perspective of Educational Psychology

Abstract: College students have taken part in less and less physical activities as a result of the common static lifestyle in recent years, lowering the level of motor function. This phenomenon has been a source of concern for schools and the government, and it is necessary to take corresponding measures to change it. The general motor function level of Chinese college students is explored first based on artificial intelligence and the human–computer interaction technology. The Physical Activity Questionnaire for Colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Studies showed that overall, the physical activity level among university students was considered satisfactory, although the percentage was slightly lower in female students (Fagaras et al 2015;Rajappan et al 2015). In recent years, college students have participated in fewer physical activities due to the typical inactive lifestyle (Ge et al 2021). Transition to college, portrayed by changes in autonomy, time constraints and financial limitations, are the barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that overall, the physical activity level among university students was considered satisfactory, although the percentage was slightly lower in female students (Fagaras et al 2015;Rajappan et al 2015). In recent years, college students have participated in fewer physical activities due to the typical inactive lifestyle (Ge et al 2021). Transition to college, portrayed by changes in autonomy, time constraints and financial limitations, are the barriers.…”
Section: Discussionmentioning
confidence: 99%
“…On the low back, three activities are not statistically significant, including class attendance (p = 0.062), sports activity (p = 0.319) and social activity on campus (p = 0.183). However, according to the study by Ge et al, [39] exercise time a day for college students significantly affects the body.…”
Section: Resultsmentioning
confidence: 99%
“…Technology allows personalization of learning so that each student can learn according to their own pace and learning style (Aeni & Yusupa, 2018;Daniel & Kamioka, 2017;. This can increase student understanding and engagement (Bajrami & Ismaili, 2016;Daryanes et al, 2023;Ge et al, 2021). As is known, that with the rapid development and also changes in technology in the current era of globalization have had a significant impact and influence on almost the entire life including the world of education (Astuti et al, 2021;Korucu & Alkan, 2018;Kounlaxay et al, 2021;Lestari, 2015).…”
Section: Discussionmentioning
confidence: 99%